Seismological and Ground Deformation Study of the Ionian Islands (W. Greece) during 2014–2018, a Period of Intense Seismic Activity - Sakkas, Vassilis; Vasilis Kapetanidis; George Kaviris; Spingos, Ioannis; Mavroulis, Spyridon; Diakakis, Michalis; Alexopoulos, John D.; Danai Kazantzidou-Firtinidou; Ioannis Kassaras; Vassilakis, Emmanuel; Dilalos, Spyridon; Kotsi, Evelina; et al. (Applied Sciences, 2022)
Seismicity in the Ionian Sea (W. Greece) is mainly generated along the Cephalonia–Lefkada Transform Fault Zone (CLTFZ) in the central Ionian, and on the northwestern termination of the Hellenic subduction margin in the south. Joint pre-, co- and post-seismic ground deformation and seismological analysis is performed at the broad Ionian area, aiming to homogeneously study the spatiotemporal evolution of the activity prior to and after the occurrence of strong (M > 6) earthquakes during the period of 2014–2018. The 2014 Cephalonia earthquakes (Mw6.1 and Mw5.9) were generated on a faulting system adjacent to CLTFZ, causing local ground deformation. The post-seismic sequence is coupled in space and time with the 2015 Lefkada earthquake (Mw6.4), which occurred on the Lefkada segment of the CLTFZ. Co-seismic displacement was recorded in the broader area. Seismicity was concentrated along the CLTFZ, while its temporal evolution lasted for several months. The 2018 Zakynthos earthquake (Mw6.7) caused regional deformation and alterations on the near-velocity field, with the seismicity rate remaining above background levels until the end of 2021. In the northern Ionian, convergence between the Apulian platform and the Hellenic foreland occurs, exhibiting low seismicity. Seismic hazard assessment revealed high PGA and PGV expected values in the central Ionian.